Elastic Membrane That Undergoes Mechanical Deformation Enhances Osteoblast Cellular Attachment and Proliferation - Toworfe, G. K.; Composto, R. J.; Lee, M. H.; Ducheyne, P. (International Journal of Biomaterials, 2010)
The main objective of this paper was to investigate the effect of transmission of force on bone cells that were attached to a deformable membrane. We functionalized a silastic membrane that measured 0.005 inches thickness and coated it with an extra cellular matrix (ECM) protein, fibronectin (FN). MC3T3-E1 osteoblast-like cells were cultured on the functionalized FN-coated membrane after which cell attachment and proliferation were evaluated. We observed an immediate attachment and proliferation of the bone cells on the functionalized membrane coated with FN, after 24 hours. Upon application of a mechanical force to cells cultured on the functionalized silicone membrane in the form of a dynamic equibiaxial strain, 2% magnitude; at 1-Hz frequency for 2 h, the osteoblast cells elicited slightly elevated phalloidin fluorescence, suggesting that there was reorganization of the cytoskeleton. We concluded from this preliminary data obtained that the engineered surface transduced applied mechanical forces directly to the adherent osteoblast cells via integrin binding tripeptide receptors, present in the FN molecules, resulting in the enhanced cellular attachment and proliferation.